2017
DOI: 10.2527/asasmw.2017.12.227
|View full text |Cite
|
Sign up to set email alerts
|

227 Compensatory body protein gain in newly weaned pigs

Abstract: Protein sources used in nursery diets are expensive; there is a need to examine alternative feeding strategies to lower production costs. Experiments were conducted to determine the effects of a short term lysine restriction at weaning on pig growth performance and body composition, and the extent of compensatory growth when pigs are then fed adequate amounts of dietary lysine. Pigs were followed until final market weight of 124kg was attained to assess effects of compensatory growth on carcass and meat qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Also, growth retardation due to nutrient limitation in weaning pigs induced compensated growth of growing-finishing pigs resulting in similar BW at the end of finishing period [ 19 , 20 ]. Weaning pigs with low growth rate due to limited nutrient intake recovered the normal growth rate compared with other pigs on the same nutritional supply [ 21 ]. Ishida et al [ 20 ] reported that compensatory growth of pigs induced by lysine sufficiency was partly attributed to greater N retention which increased protein synthesis in skeletal muscle.…”
Section: Resultsmentioning
confidence: 99%
“…Also, growth retardation due to nutrient limitation in weaning pigs induced compensated growth of growing-finishing pigs resulting in similar BW at the end of finishing period [ 19 , 20 ]. Weaning pigs with low growth rate due to limited nutrient intake recovered the normal growth rate compared with other pigs on the same nutritional supply [ 21 ]. Ishida et al [ 20 ] reported that compensatory growth of pigs induced by lysine sufficiency was partly attributed to greater N retention which increased protein synthesis in skeletal muscle.…”
Section: Resultsmentioning
confidence: 99%